Community characteristics of phytoplankton and eutrophication assessment in Tianjin section, downstream of Haihe River Basin - Yong Dou; Wen L. Zhou (Journal of Freshwater Ecology, 2022)
With the aim of exploring the features of the phytoplankton community and eutrophication status in the lower reaches of the Haihe River Basin near Tianjin, sampling surveys were carried out in May, July and September of 2021. The results showed 53 dominant phytoplankton species in the survey area, of which 36 species were found in May, while 28 were found both in July and September. Ten dominant species were highlighted in the surveys, mainly belonging to Cyanophyta, Chlorophyta, Bacillariophyta, and Cryptophyta. The regions with relatively higher levels of phytoplankton biomass and abundance were Duliujian River, Qilihai Wetland and New Chaobai River, while the highest species richness and biodiversity occurred in Yuqiao Reservoir, Duliujian River, New Chaobai River and Ji Canal. The highest TN content was observed in Duliujian River, and the highest TP, chl-a, CODMn and EI were recorded in New Chaobai River. In contrast, the region with the lowest level of eutrophication was Yuqiao Reservoir. Correlation analysis and RDA analysis showed that the eutrophication assessment indices affecting the phytoplankton community and distribution of dominant species were mainly TN, chl-a and CODMn in May and July, while TN, TP, chl-a, CODMn and EI were the most influential in September.